2020
DOI: 10.3390/jcm9103380
|View full text |Cite
|
Sign up to set email alerts
|

Partial Achilles Tendon Rupture—A Neglected Entity: A Narrative Literature Review on Diagnostics and Treatment Options

Abstract: Partial ruptures in the Achilles tendon are rather uncommon and are often misinterpreted as aggravated Achilles tendinopathy, and not always considered as a differential diagnosis. The aim of this literature review was to characterize typical symptoms, to provide an overview of available diagnosis and treatment options, and to give reference points for future research. There were few studies and sparse knowledge of scientific value, making it difficult to give evidence-based recommendations. Based on the few s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
33
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 49 publications
0
33
0
2
Order By: Relevance
“…Bmode might not adequately differentiate between partial tendon tears from local degenerative lesions, as has been shown previously. 16,34 However, we did not confirm the presence of partial ruptures by biopsies or intraoperative findings, and further research is required to assess the capacity of high-frequency ultrasound probes in detecting partial ruptures. 16 Interestingly, the quantitative MRI parameters CSA (79%) and AP diameter (59%) showed good to moderate diagnostic accuracy for insertional and midportion AT monitoring, respectively.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…Bmode might not adequately differentiate between partial tendon tears from local degenerative lesions, as has been shown previously. 16,34 However, we did not confirm the presence of partial ruptures by biopsies or intraoperative findings, and further research is required to assess the capacity of high-frequency ultrasound probes in detecting partial ruptures. 16 Interestingly, the quantitative MRI parameters CSA (79%) and AP diameter (59%) showed good to moderate diagnostic accuracy for insertional and midportion AT monitoring, respectively.…”
Section: Discussionmentioning
confidence: 59%
“… 16 , 34 However, we did not confirm the presence of partial ruptures by biopsies or intraoperative findings, and further research is required to assess the capacity of high-frequency ultrasound probes in detecting partial ruptures. 16 Interestingly, the quantitative MRI parameters CSA (79%) and AP diameter (59%) showed good to moderate diagnostic accuracy for insertional and midportion AT monitoring, respectively. This is in line with previous studies that showed a significant decrease of tendon volume and CSA after 24 weeks of eccentric exercises.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…This suggests that ED clinicians and practitioners do possess expertise for assessment of these injuries and should not be considered "non-specialists". The fact that one partial thickness tear was initially discharged is unsurprising as these are known to be more problematic to diagnose clinically, with symptoms easily misinterpreted as aggravated Achilles tendinopathy [14]. Unfortunately, it was beyond the audit scope to determine if any of the patients who initially presented via other referral routes had their initial referral delayed for any reason.…”
Section: Discussionmentioning
confidence: 99%